Design Thinking as a Means of Citizen Science for Social Innovation - Goi, Hoe Chin; Tan, Wee-Liang (Frontiers in Sociology, 2021)
Members of the public or community can play a significant role in the development of social innovations. When a social innovation is developed involving a scientific approach and the community, there is the confluence of two fields-citizen science and social innovation. Social innovations can be developed through the employment of design-thinking. In this paper, we advocate design thinking as an approach to marry the two fields for a desired outcome of improved community life in ageing housing estates in Tokyo. The two fields, citizen science and social innovation, are described in brief before the design thinking method is introduced and its utility in engaging citizens for social innovation is explored. The paper provides two case illustrations and the lessons drawn from them. We conclude with pointers for others who desire to employ this approach. When the resultant innovation and design-thinking approach are adopted by the community for future projects, there could be a change in society and possible forward movement for self-help and change.